Patterns of populist mobilization: comparing narratives on COVID-19 in the global South - BELDER, FERİT (My University, 2023)
This article explores the narratives shaping the official discourse on COVID-19 in five countries governed by populists in different world regions. It is based on the assumption that a crisis like the pandemic constitutes a perfect occasion for populist mobilization, allowing populist leaders to construct reality in their favour by deliberately promoting own narratives about the pandemic, its origin and management. Analyzing 357 original-language speeches and statements by representatives of the populist governments of Brazil, Israel, India, Mexico and Turkey, the article shows that populists in power use crises to mobilize support in very different ways. Surprisingly, most populist governments neither resorted to anti-scientific claims or conspiratorial discourses attributing the crisis to obscure elites, nor blamed minorities not belonging to the \"true people\". By contrast, except for Bolsonaro in Brazil, all other populist governments tried to mobilize support by emphasizing the strength of the \"people\" or even by promoting an inclusive discourse of national unity, leaving aside the more divisive elements of their general populist discourse. Based on the cases analysed, the article concludes by developing hypotheses on the possible drivers of such variations in patterns of populist mobilization.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Sociology; Political Science; International Relations; ULUSLARARASI İLİŞKİLER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); INTERNATIONAL RELATIONS; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Social Sciences & Humanities; Global South politics; global health; domestic politics; POLITICS; PARTIES; EUROPE